Observing the Invisible : Poems - Cherry, Kelly (Book collections on Project MUSE., 2020)
"In Observing the Invisible, Kelly Cherry offers poems that explore the realms of modern and contemporary physics, confronting the invisibilities and mysteries of the material world. She leverages challenging ideas into a space of contemplative wonder as the book moves from external observation into an increasingly inward space of personal reflection and expression"--